Poziom agresywności kobiet uprawiających sporty rodzajowo męskie i kobiece = The level of social aggressiveness in women practising male or female sports - Zuzanna Mazur; Natalia Organista (Kazimierz Wielki University, 2015)
Mazur Zuzanna, Organista Natalia. Poziom agresywności kobiet uprawiających sporty rodzajowo męskie i kobiece = The level of social aggressiveness in women practising male or female sports. Journal of Education, Health and Sport. 2015;5(5):151-164. ISSN 2391-8306. DOI 10.5281/zenodo.17473 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A151-164 https://pbn.nauka.gov.pl/works/559232 http://dx.doi.org/10.5281/zenodo.17473 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.04.2015. Accepted: 08.05.2015.   Poziom agresywności kobiet uprawiających sporty rodzajowo męskie i kobiece   The level of social aggressiveness in women practising male or female sports   Zuzanna Mazur (zuzanna.mazur@op.pl) Natalia Organista (natalia.organista@gmail.com)   Akademia Wychowania Fizycznego w Warszawie University of Physical Education in Warsaw   Słowa kluczowe: kobieta, agresywność, sporty rodzajowo męskie, sporty rodzajowo kobiece. Keywords: woman, aggressiveness, male sports, female sports. Streszczenie   Wprowadzenie Jednym z podstawowych aspektów czy też skutków uprawiania sportu wyczynowego, który przynależy do stereotypu "męskości", jest agresywność. Jej instrumentalny charakter ujawnia się zarówno w działaniach związanych z rywalizacją, jak i w postawie autonomii poglądów i przekonań czy też ignorowaniu praw i racji innych. Zastanawiające wydaje się, czy podobny poziom agresywności ujawniają kobiety trenujące wyczynowo sporty rodzajowo męskie (boks, żużel, podnoszenie ciężarów) w porównaniu z kobietami uprawiającymi sporty rodzajowo kobiece (gimnastyka artystyczna, pływanie synchroniczne).   Cel pracy Podstawowym celem badań jest poznanie różnicy w poziomie agresywności kobiet w zależności od uprawianej dyscypliny.     Materiał i metody W badaniach brały udział kobiety trenujące dyscypliny rodzajowo męskie (kick- boxing, zapasy; n=30) oraz rodzajowo kobiece (gimnastyka artystyczna, pływanie synchroniczne; n=40). Do oceny nasilenia oraz struktury agresji zastosowano Kwestionariusz "Nastroje i Humory" A.H. Bussa i A. Durkee.   Wyniki Badania wykazały wyższy poziom agresywności u przedstawicielek dyscyplin męskich, przejawiający się głównie w większej napastliwości fizycznej.   Wnioski Kobiety uprawiające sporty rodzajowo nieadekwatne różnią się pod względem agresywności od kobiet trenujących sporty kobiece. Zapaśniczki i kick-boxerki cechuje wyższy poziom zachowań agresywnych, przejawiający się głównie w napastliwości fizycznej. Może mieć to związek ze specyfiką uprawianych dyscyplin, w których dochodzi do bezpośredniego kontaktu z przeciwnikiem.   Abstract Introduction One of the main aspects or effects of practising a professional sport, which belongs to the "masculinity" stereotype, is aggressiveness. The instrumental character of aggressiveness takes place not only in competition- related activity, but also in the autonomy attitude of the views and conviction as well as ignoring the rights and reason of others. It seems puzzling whether a similar level of aggressiveness is represented by women training competitive male sports (box, motorcycle races, wrestling) in comparison with women training female sports (rhythmic gymnastics, synchronized swimming).   Purpose of the study The main objective of the study is to find a difference in the level of women's aggressiveness depending on the sport practiced.   Material and methods Women practising male sports (kick- boxing, wrestling; n=30) and female sports (rhythmic gymnastics, synchronized swimming; n=40) participated in the study. To assess the severity and structure of aggressiveness The Questionnaire "Moods and Temper" by A.H. Buss and A. Durkee was used.   Results The study stated the higher level of aggressiveness (mainly the physical one) in women practising kick- boxing and wrestling.   Conclusions Women training gender inadequate sports differed significantly in the level of aggressiveness from women practising gender adequate sports. Wrestlers and kick- boxers have the higher level of aggressive behavior, manifested particularly in the physical aggressiveness. It may be related to the specific features of these disciplines with direct contact, oriented towards  the opponent's body.